Low-dose microcystin-LR antagonizes aflatoxin B1 induced hepatocarcinogenesis through decreasing cytochrome P450 1A2 expression and aflatoxin B1-DNA adduct generation. (June 2020) - Wang, Lingqiao; He, Lixiong; Zeng, Hui; Fu, Wenjuan; Wang, Jia; Tan, Yao; Zheng, Chuanfen; Qiu, Zhiqun; Luo, Jiaohua; Lv, Chen; Huang, Yujing; Shu, Weiqun
Abstract: Aflatoxin B1 (AFB1) and microcystin-LR (MC-LR) co-existed in food and water, and were associated with hepatocellular carcinoma (HCC). AFB1 induced HCC by activating oxidative stress and generating AFB1-DNA adducts, while MC-LR could promote HCC progression. However, whether they have co-effects in HCC progression remains uncertain. In this study, we found the antagonistic effects of MC-LR on AFB1 induced HCC when they were exposed simultaneously. Compared with single exposure to AFB1, co-exposed to MC-LR significantly repressed the AFB1 induced malignant transformation of human hepatic cells and the glutathione S-transferase Pi positive foci formation in rat livers. MC-LR inhibited AFB1 induced upregulation of cytochrome P450 family 1 subfamily A member 2 (CYP1A2) and reduced the AFB1-DNA adducts generation in both human hepatic cells and rat livers. These results suggest that when co-exposure with AFB1, MC-LR might repress hepatocarcinogenicity of AFB1, which might be associated with its repression on AFB1 induced CYP1A2 upregulation and activation. Highlights: AFB1 and MC-LR co-exist in food and water in humid and warm areas. Co-exposed to MC-LR antagonize hepato-carcinogenicity of AFB1 . MC-LR repress AFB1 induced upregulation and activation of CYP1A2. MC-LR inhibit the formation of AFB1-DNA adducts.